Physico-Chemical and Tribological Studies of Hydraulic Fluid Based Wasted Vegetable Oil - Sermpanichakit, Apichart; Prabkaew, Chamlong (วารสารสมาคมวิศวกรรมเกษตรแห่งประเทศไทย, 2017)
The main reason of several researches shows the plant oil as main ingredient into lubrication and hydraulic fluid because of good lubricating properties, non-toxic and biodegradability to substitute for the petroleum-based oil that has limited resources; but, there was no any researches to study in using of the wasted vegetable oil. The aim of this paper was to investigate the physio-chemical and tribological properties by CSM tribometer (Ball-on-disk) of hydraulic fluid based wasted vegetable oil. The wasted vegetable oil used for cooking many repeated time at the fresh market was studied and then it was made to be biodiesel by trans esterification process, but the limited range of biodiesel viscosity and this is constrains their use as suitable biolubricants in hydraulic system. Adding of 5% wt ethylene-vinyl acetate copolymer (EVA) into this biodiesel was studied. It has been found that the viscosity of the biodiesel could increase from 5.81 to 48.6 cSt at 40oC. When consider in the viscosity, there are 3 samples from all hydraulic oil in this research which are near to the local commercial hydraulics oil no.46 and 68, were studied. The flush point was also higher than Thai Indusrial Standard; but, pour point might be a problem. The coefficient of friction and wear volume of all three samples stay in the ranges 0.10 - 0.14 and 0.006 – 0.023 mm3 respectively; and better lubricity more wear resistance than PTT68 as 0.155 and 0.037 mm3 respectively at the same testing conditions. This is indicated in the hydraulic fluid based wasted vegetable oil was a good potential to substitute for local commercial petroleum-based oil.